Efficacy and safety evaluation of Cimicifuga foetida extract in menopausal women. (2nd January 2018) - Gao, L.; Zheng, T.; Xue, W.; Wang, Y.; Deng, Y.; Zuo, H.; Sun, A.
Abstract: Objective: The aim of this study was to evaluate the efficacy and safety of long-term treatment with Cimicifuga foetida extract in menopausal women. Methods: A prospective, randomized, controlled clinical trial was conducted. A total of 96 early postmenopausal women were randomly assigned to three groups: group A received 1 mg estradiol valerate daily plus 4 mg medroxyprogesterone acetate on days 19–30; group B received 1 mg estradiol valerate daily plus 100 mg micronized progesterone on days 19–30; group C received 100 mg C. foetida extract daily. The efficacy was evaluated. Safety parameters were recorded. Results: A total of 81 patients completed the treatment and follow-up visit. The modified Kupperman Menopausal Index scores decreased after 3 months in all groups. No significant changes were observed in the liver, renal function and components of metabolic syndrome in group C ( p  > 0.05). There were no significant differences in the incidences of metabolic syndrome among the three groups ( p  > 0.05). After 24 months, the endometrial thickness increased significantly in group B ( p  = 0.014), but not in the C. foetida extract group ( p  > 0.05). Conclusions: C. foetida extract is safe and effective for the treatment of menopausal symptoms in postmenopausal women.